Transport lotniczy materiałów medycznych samolotem Preighter w pandemii Covid-19 - Augustyn Sławomir; Firlej Mikołaj; Alomar Iyad (2022)
Air transport plays a significant role in supply chain cargo. It is used for the carriage of dangerous goods e.g., medical supplies. Its role gained particular importance when the Covid-19 pandemic led to a drastic decline in air operations. In response to the crisis, many air carriers temporarily converted passenger aircraft to preighter aircraft. Due to safety regulations, rising freight prices and easing of restrictions on travel, there is a perceived decline in interest in transporting cargo using such a type of aircraft. The aim of the research was to indicate the role of preighter aircraft in the transport of medical supplies in the Covid-19 pandemic. The research problem was formulated in the form of a question: What conditions made preighter aircraft play a leading role in the transport of medical supplies in the Covid-19 pandemic? The publication adopted the following hypotheses: 1. The participation of preighter aircraft in the Covid-19 pandemic depends on the increase in infections. 2. International and European aviation regulations only regulate guidelines for the carriage of cargo using passenger seats. 3. Due to the specific nature of the transport of Covid-19 vaccines, their safe delivery is guaranteed by thermal shipping container. The following research methods have been used in the publication: analysis and synthesis, comparison, search of normative acts and literature on the subject, abstraction, and inference. The authors hope the results obtained from the conducted research and the presented considerations will constitute a starting point for further scientific research on the discussed subject.